The Development of the Constituent Social Class as Political Participation in Banda Aceh and Meulaboh - Rena Juliana; Reni Juliani; Nurkhalis Nurkhalis (Prodi Sosiologi FISIP Universitas Teuku Umar, 2021)
Indonesia adheres to a democratic system of government. Each citizen, on the basis of the choice of ordinary people, chooses free political participation and then changes their direction as a sympathizer. Today, the excitement of political participation in Indonesian society to spread on Aceh has been somewhat hurt because some people have changed the political climate to be bad. This is reflected in the previous political participation side by side to deliver rhetoric to reap the voice of the people, but it has become a competition for each other. The purpose of this study is to find out what types of political participation occurred in constituents in Banda Aceh and West Aceh and who are the actors or groups that weaken or strengthen political participation in the constituents. The research method used is a qualitative approach with informants consisting of key informants, subject informants and non-subject informants. The results showed that the types of political participation in the constituents of Banda Aceh and West Aceh were very different and that sympathizers and political actors continued to strengthen and weaken the constituents. It is expected that this research will be a comparative study of the dynamics of policy in the Aceh region.